STUDY OF MAINTAINING CONFIDENTIALITY DURING CHANGE OF INFORMATION (International Journal of Engineering and Computer Science, 2017)
In this modern era, collection of information and its maintenance is a very tough job. Whenever information is gathered for some important work, there arises a need for confidentiality. People ignore some basic points which should be kept in mind while data is collected, executed and exchanged. These points are mentioned in this paper and if taken in consideration they can help you to maintain privacy of your data.